Packaging systems and storage times serve as post-lethality treatments for Listeria monocytogenes on whole muscle beef jerky - A. Lobaton-Sulabo; T. Axman; Kelly J.K. Getty; Elizabeth A.E. Boyle; N. Harper; K. Uppal; B. Barry; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 2010)
Following several outbreaks involving Listeria monocytogenes in ready-to-eat meat and poultry products, the United States Department of Agriculture Food Safety and Inspection Service required that processors of these products implement post-processing intervention strategies for controlling L. monocytogenes. The USDA defines a postlethality treatment as a process that reduces L. monocytogenes by at least 1 log. Research has shown that packaging can generate a 1 log L. monocytogenes reduction following 1 or more weeks of storage at room temperature. The objective of our study was to determine the effect of packaging system and storage time on reducing L. monocytogenes on shelf-stable whole muscle jerky.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; Listeria monocytogenes; Beef jerky